(untitled) (International Current Pharmaceutical Journal, 2015)
Pregnancy-induced hypertension (PIH) and gestational diabetes mellitus (GDM) both have no adequate classification in addition to nomenclature that creates difficulties for researchers to find link between them. Aim of this work was to review the most recent data available on PIH and GDM and find the association between both conditions during gestation. Epidemeologies and whole studies which have done till now days, could not satisfy that what is association between PIH and GDM. The main issue to solve is how to find the association between GDM and PIH. Very limited data and research studies are available, creating hindrance to find any association. The one way to find the association now, can be that it should be checked the level of hypertension before, during and after gestation. According to the available data and research, it could be deduced that insulin resistance, present in non-insulin dependent diabetes mellitus (NIDDM), may provide association more frequently. However, no direct evidential data is available for this link. Perveen et al., International Current Pharmaceutical Journal, October 2015, 4(11): 453-456